The effect of thermoforming temperature and mould vent hole to the thermoplastic container made of 1 mm polypropylene (PP) sheet - Sa’id Badi’urzaman, Hasanuddin (2016)
Polypropylene is in a category of thermoplastic polymer resin. It is a part of both the average household and is in commercial and industrial applications. This plastic is regularly used for food containers because it needs to be dishwasher safe. Although the thermoforming process has been developed for over two decades but there are still some unsolved problems found in this technology. In the development commercial polypropylene grades, there are several critical problems addressed such as sheet quality, part uniformity and wall thickness, regrind use and dimensional stability. This project starts with searching various types of journal that related to the topic of designing and fabricating thermoplastic container using polypropylene (PP) sheet via thermoforming process. Read and understand all the journals are the element in the effort to make this project. This study aims to design and fabricate plastic container using polypropylene (PP) sheet with thickness 1 mm via thermoforming process. CATIA P3 V5R21 software by Dassault Systemes was used to design the plastic container and its mould. Design consideration for the plastic product and its mould is important as to reduce the defects. For example fillet was added to avoid sharp edge. Draft angle also was used at the wall side of mould which is to ease the process of absorption. Round shape plastic container was selected to be design as it has smooth shape that allows the pliable polypropylene sheet to form according to the shape of the mould. An aluminum block with dimension 100 mm x 100 mm x 50 mm was used as the female cavity been cut using band saw machine. The aluminum blocks was machined using Makino KE55 CNC Milling Machine located at the Machining Laboratory. High Speed Drilling machine was used to drill the hole at the bottom of the female mould. 1 mm and 6 mm diameter of drill bits was used to make the holes at the bottom of aluminum mould. Moreover, this project studies the effect of thermoforming temperature and number of mould vent hole to 1 mm PP sheet. Two types of vent holes used on the aluminum mould which are 1 vent and 5 vent holes. There were two parameters used to fabricate polypropylene plastic container. The first parameter is the different degree of temperature used to heat the 1 mm polypropylene plastic sheet. The degree of temperature used is 160°C, 165°C, 170°C, and 175°C. The second parameter that was used is different number of vent holes on the mould to fabricate the plastic container. The first one is 1 hole and secondly 5 holes, both ways was used same diameter of the vent hole which is 1mm. Lastly the process to investigate the hardness property on the fabricated polypropylene plastic container was conducted using the Vickers Micro Hardness Tester to obtained the hardness value. Lowest value of HV range shows that the polypropylene plastic containers have uniform hardness. Based on the research conducted, the appearance of polypropylene plastic container at temperature 165°C for 5 vent holes on mould almost goods compare to others temperature used. The appearance for other temperature was showed some defects such like wrinkles and overheated.